Detecting protein analytes that modulate transmembrane movement of a polymer chain within a single protein pore. - Movileanu, L; Howorka, S; Braha, O; Bayley, H (2000)
Here we describe a new type of biosensor element for detecting proteins in solution at nanomolar concentrations. We tethered a 3.4 kDa polyethylene glycol chain at a defined site within the lumen of the transmembrane protein pore formed by staphylococcal alpha-hemolysin. The free end of the polymer was covalently attached to a biotin molecule. On incorporation of the modified pore into a lipid bilayer, the biotinyl group moves from one side of the membrane to the other, and is detected by reversible capture with a mutant streptavidin. The capture events are observed as changes in ionic current passing through single pores in planar bilayers. Accordingly, the modified pore allows detection of a protein analyte at the single-molecule level, facilitating both quantification and identification through a distinctive current signature. The approach has higher time resolution compared with other kinetic measurements, such as those obtained by surface plasmon resonance.